Dynamics of HDL-Cholesterol Following a Post-Myocardial Infarction Cardiac Rehabilitation Program - Carlos Bertolín-Boronat; Héctor Merenciano-González; Víctor Marcos-Garcés; María Luz Martínez-Mas; Josefa Inés Climent Alberola; Nerea Pérez; Laura López-Bueno; María Concepción Esteban-Argente; María Valls Reig; Ana Arizón Benito; Alfonso Payá Rubio; César Ríos-Navarro; et al. (Reviews in Cardiovascular Medicine)
Background: Exercise-based cardiac rehabilitation programs (CRP) are recommended for patients following acute coronary syndrome to potentially improve high-density lipoprotein cholesterol (HDL-C) levels and prognosis. However, not all patients reach target HDL-C levels. Here we analyze the dynamics and predictors of HDL-C increase during CRP in patients following ST-segment elevation myocardial infarction or occlusion myocardial infarction. Methods: We conducted a prospective study of myocardial infarction patients who completed exercise-based Phase 2 CRP. Data was collected on clinical variables, cardiovascular risk factors, treatment goals, pharmacological therapy, and health outcomes through questionnaires at the beginning and at the end of Phase 2 CRP. Lipid profile analysis was performed before discharge, 4 to 6 weeks after discharge, and at the end of Phase 2 CRP. Changes in lipid profiles were evaluated, and predictors of failure to increase HDL-C levels were identified by binary logistic regression analysis. Results: Our cohort comprised 121 patients (mean age 61.67 ± 10.97 years, 86.8% male, and 47.9% smokers before admission). A significant decrease in total cholesterol, triglycerides, and low-density lipoprotein cholesterol (LDL-C) were noted, along with an increase in HDL-C (43.87 ± 9.18 vs. 39.8 ± 10.03 mg/dL, p < 0.001). Patients achieving normal HDL-C levels (>40 mg/dL in men and >50 mg/dL in women) significantly increased from 34.7% at admission to 52.9% the end of Phase 2. Multivariable analysis revealed smoking history (hazard ratio [HR] = 0.35, 95% confidence interval [CI], 0.11–0.96, p = 0.04), increased reduction in total cholesterol (HR = 0.94, 95% CI, 0.89–0.98, p = 0.004), and increased reduction in LDL-C (HR = 0.94, 95% CI, 0.89–0.99, p = 0.01) were inversely associated with failure to increase HDL-C levels. Conversely, higher HDL-C before CRP (HR = 1.15, 95% CI, 1.07–1.23, p < 0.001) and increased lipoprotein (a) (HR = 1.01, 95% CI, 1–1.02, p = 0.04) predicted failure to increase HDL-C levels. No significant correlations were found with Mediterranean diet adherence, weekly physical activity, training modalities, or physical fitness parameters. Conclusions: Participation in an exercise-based Phase 2 CRP led to mild but significant increases in HDL-C. Smoking history and patients experiencing substantial reductions in total cholesterol and LDL-C were more likely to experience HDL-C increases, unlike those with higher HDL-C and lipoprotein (a) levels before CRP.